Design and Fuzzy Delphi Validation of an Augmented Reality Ergonomics Training Module for Manual Material Handling Workers - Norman, Fatimah Zahra; Yasin, Siti Munira; Mohamad, Mariam; Azzani, Meram (Malaysian Journal of Medical Sciences, 2026)
Background: Manual material handling (MMH) workers are at high risk of developing work-related musculoskeletal disorders (WMSDs) resulting from repetitive lifting, awkward postures, and physically demanding tasks. Traditional ergonomics training methods are less engaging and may not effectively translate knowledge into safe workplace practices. This study aimed to develop and validate an Augmented Reality Physical Ergonomics (ARPE) training module to improve ergonomics knowledge, self-prevention behaviours, and self-evaluation skills among MMH workers.Methods: The ARPE module was structured around three domains (knowledge, self-prevention, and self-evaluation), comprising 25 subdomains identified through a systematic review of ergonomics guidelines and relevant studies. Content validation was performed using the fuzzy Delphi method with a panel of 10 multidisciplinary experts. The relevance and clarity of each item were evaluated by the experts on a 7-point Likert scale. Responses were converted into triangular fuzzy numbers and analysed using consensus criteria of threshold values (d) ≤ 0.20, ≥ 75% expert agreement and α-cut ≥ 0.50.Results: All 25 subdomains achieved expert consensus, confirming their relevance for ergonomics training among MMH workers. The validated framework emphasises knowledge of WMSDs and risk factors, proactive ergonomic practices, and workers’ ability to assess and adjust handling techniques.Conclusion: The content validity of the ARPE module was confirmed, and a comprehensive foundation for immersive ergonomics training was established. Pilot trials and long-term studies are needed to evaluate the module’s usability among MMH workers and to assess its practicality, user acceptance, and effectiveness in improving workplace ergonomic practices.